Implementasi Metode Self Directed Learning dan Diskusi Kelompok Kecil Dalam Rangka Meningkatkan Kompetensi Menerapkan Konsep Model Keperawatan Dalam Berbagai Situasi Pada Mata Ajar Ilmu Keperawatan Dasar II - Insiyah Insiyah ((JKG) Jurnal Keperawatan Global, 2016)
Abstract: Self Directed Learning, Small Group Discussion, Basic Nursing Science II. Basic Nursing Science II, is a subject for nursing students in Diploma IV This is a new subject based on curriculum 2014 containing of important concepts such as nursing theory that sometimes it is difficult for student to learn. Commonly students encounter difficulties in this subject so that they are not interested in it. They think that this subject is difficult to be understood because it contains of concepts. The aims of this research is to identify the success of learning methods by using self directed learning and small group discussion in order to increase student ability to achieve competence in application of conceptual nursing model in any situation. This research is Classroom Action Rersearch design. The result show that self directed learning and small group discussion methods are the learning methods that can increase student activity in learning process and improve student ability to achieve competence in application of conceptual nursing model in any situation.